The Influence of Work Motivation and Career Development on Employee Performance at PT Bank DKI Syariah KCP Cengkareng West Jakarta - Lestari, Ayu; Tilova, Nurdinni (Transforma Jurnal Manajemen, 2025)
This study aims to analyze the influence of Work Motivation and Career Development on employee performance at PT Bank DKI Syariah Cengkareng, West Jakarta. This study uses a Quantitative method with an Associative approach. Data were collected from 42 Respondents through a Questionnaire on Work Motivation (X1), Career Development (X2), and Employee Performance (Y). Data analysis includes Validity Test, Reliability, Classical Assumptions, Regression, Correlation Coefficient, Determination Coefficient, and Hypothesis. The results of the study show that Work Motivation has a significant influence on employee performance, with a determination coefficient value of 14.4% and a hypothesis test obtained t count > t table (2.594 > 2.023). Career Development has a significant effect on employee performance, with a determination value of 63.2% and a hypothesis test t count > t table (8.296 > 2.023). Simultaneously, Work Motivation and Career Development have a significant effect on employee performance with regression Y = = 8.648 + 0.150X1 + 0.784X2 and a coefficient of determination of 65.2% while the remaining 34.8% is caused by other factors not examined by the author, meaning that if there is an increase in the variables of Work Motivation and Career Development, employee performance will also increase. Hypothesis testing obtained the value of F count > F table (36.599 > 3.24). it can be concluded that Work Motivation (X1) and Career Development (X2) simultaneously have a positive and significant effect on employee performance (Y).